Pengaruh Work-Life Balance Dan Iklim Organisasi Terhadap Kepuasan Kerja Pada Tenaga Kependidikan Universitas Airlangga - Sabila Rosida, Salwa; Chusairi , Achmad (CV RIFAINSTITUT, 2023)
This study aims to determine the effect of work-life balance and organizational climate on job satisfaction in airlangga university educational staff. The hypotheses in this study are (1) work-life balance and organizational climate simultaneously affect job satisfaction: (2) work-life balance affect job satisfaction; and (3) organizational climate affects job satisfaction in airlangga university educational staff. The method in this study use quantitative research methods. The subjects in this study were 250 education staff working at airlangga university. The measurement tools used Work-life Balance (WLB), Organizational Climate Measure (OCM), Facet Satisfaction Scale (FSS). Data analysis used multiple liniear regression tests with IBM SPSS Statistic 27 for MAC. The results of data analysis show that work-life balance and organizational climate silmutaneously have a significant effect on job satisfaction of 0,000. Work-life balance shows a positive and significant influence on job satisfaction of 0,000, meaning that the higher the work-life balance, the higher the level of job satisfaction. Organizational climate shows a postifive and significant influence on job satisfaction of 0,000, meaning that the higher the organizational climate, the higher the level of job satisfaction.